2013
DOI: 10.4172/2155-6199.1000188
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Subspecies of Staphylococcus aureus from Sediments of Lanzhou Reach of the Yellow River Aerobically Reduces Hexavalent Chromium

Abstract: Background: Lanzhou reach of the Yellow River is contaminated by heavy metals including chromium perennially. The microbial community within the sediment is very active. Yet the study on the bacteria in this distinctive microbial community is still scarce.Results: LZ-01, a Gram-positive hexavalent chromium-reducing bacterium was isolated from the soil sample collected at a petrochemical corporation wastewater discharge site of Lanzhou reach. It was able to aerobically reduce 94.5% of 0.4 mM Cr (VI) to Cr(III) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(25 citation statements)
references
References 51 publications
0
25
0
Order By: Relevance
“…Lanzhou reach of the Yellow River is heavily contaminated by industrial wastes. Bacteria previously isolated from this environment showed heavy metal resistance and remediation potential (Zhang et al 2013). In this Figure 2 Microbial growth of strain LZ-11 monitored by spectrophotometer (optical density, OD) at 600 nm under different Cd(II)concentrations.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Lanzhou reach of the Yellow River is heavily contaminated by industrial wastes. Bacteria previously isolated from this environment showed heavy metal resistance and remediation potential (Zhang et al 2013). In this Figure 2 Microbial growth of strain LZ-11 monitored by spectrophotometer (optical density, OD) at 600 nm under different Cd(II)concentrations.…”
Section: Discussionmentioning
confidence: 94%
“…Bacteria previously isolated from this environment showed heavy metal resistance and remediation potential (Zhang et al . ). In this study, we have isolated bacteria with high resistance to Cd(II).…”
Section: Discussionmentioning
confidence: 97%
“…It can also grow under acidic conditions at pH 5 (Zhang et al . ). These results indicated that strain LZ‐01 has high U(VI) resistance and is likely to be able to survive in nuclear waste.…”
Section: Resultsmentioning
confidence: 97%
“…Staphylococcus aureus LZ‐01 was isolated from the Lanzhou reaches of the Yellow River (36°06′N, 103°39′E) (Zhang et al . ). Staphylococcus aureus ATCC25923 and E. coli DH5 α were used as reference strains.…”
Section: Methodsmentioning
confidence: 97%
See 1 more Smart Citation